Особливості біоелементного складу тканини щитоподібної залози, кісток і волосся у жителів Прикарпаття з автоімунним тиреоїдитом Хашимото - Якимець, Н. С. (Clinical Endocrinology and Endocrine Surgery, 2010)
For the first time it was conducted complex definition of the trace elements (Cr, Mn, Cu, Zn, Ni and Co) in thyroid gland tissue, bone tissue and in a hair of individuals without thyroid pathology and with Hashimoto autoimmune thyroiditis who live in Precarpathian endemic region. It was established that disbalance of zinc, cuprum, magnum, cobalt, nickel takes principal role in pathogenesis of Hashimoto autoimmune thyroiditis among inhabitants of Precarpathian region that can be marker of thyroid autoimmune diseases development.